The cervical spine in patients with psoriatic arthritis: a clinical, radiological and immunogenetic study. Issue 1 (January 1992) - Salvarani, C; Macchioni, P; Cremonesi, T; Mantovani, W; Battistel, B; Rossi, F; Capozzoli, N; Baricchi, R; Portioli, I
Abstract : The radiological changes of the cervical spine were evaluated in 57 patients with psoriatic arthritis and were correlated with clinical, radiological, and immunogenetic features of the disease. Forty patients (70%) showed radiological evidence of the cervical spine being affected by the disease. Two patterns of cervical spine abnormalities were noted. Fifteen patients (26%) had erosive and/or subluxing cervical rheumatoid like lesions; 25 patients (44%) had a more frequently reported pattern similar to ankylosing spondylitis. Although subaxial subluxations were the most frequently observed cervical abnormalities (53%) in the inflammatory subgroup, none of the patients studied had cord compression. Ankylosing cervical spine disease was the only form of axial involvement in nine (36%) of 25 patients with the ankylosing form of psoriatic arthritis. All of these patients had peripheral disease and were B27 negative. Predictors of cervical spine disease patterns were considered using clinical, demographic, and radiological features and HLA antigens. The results of a multivariate analysis showed that the best predictors of inflammatory cervical spine disease are the presence of HLA-B39 and HLA-DR4 antigens, radiocarpal erosions, and the absence of the HLA-DR5 antigen.